Breaking Psychological Contracts with the Burden of Workload: A Weekly Study of Job Resources as Moderators. Issue 1 (20th July 2016) - Bal, P. Matthijs; Hofmans, Joeri; Polat, Tuğba
Abstract : This intra‐individual study examined relationships over time of job demands and resources with employee perceptions of psychological contract breach and violation, or the emotional impact of breach. Based on Conservation of Resources (COR) Theory, we expected job demands to increase the susceptibility of experiencing contract breach and violation over time, and we expected this relationship to be moderated by available job resources. In particular, autonomy and social support were expected to buffer relationships of job demands with breach, while development was expected to intensify relationships between job demands and breach. For violation, we expected job resources to intensify the relationships between job demands and breach, in line with the betrayal hypothesis. Analyses on weekly diary data showed that weekly job demands were related to higher contract breach perceptions in the following week when autonomy and social support were low and when development was high. Moreover, weekly job demands were related to higher violation in the next week, especially when social support was high. The study shows that job demands may be related to higher odds of experiencing a breach and higher violation, and job resources may play opposite roles in moderating the relationships of job demands with breach and violation.